Developing Students’ Speaking Skill through Small Group Discussion (SGD) Technique - Chelsea Valentine; Jamiluddin Jamiluddin; Wahyudin Wahyudin; Mochtar Marhum (Universitas Cokroaminoto Palopo, 2023)
The purpose of this research is to find out whether or not the use of Small Group Discussion (SGD) technique can develop speaking skill to the tenth grade students of SMA Negeri 1 Bolano Parigi Moutong District. This research used a quasi-experimental research design with 77 students as a sample selected by using the cluster sampling technique. Additionally, the data of this research was obtained through a test which was divided into pre-test and post-test. The mean pre-test score for the experimental group and the control group were 48.90 and 55.77. The mean post-test score for the experimental group and the control group were 73.90 and 60.04. The data was theoretically analyzed by applying the t-test formula where the degree of freedom (df) is 75. The result of statistical analysis shows that the t-test value is 3.19 while the t-table value is 1.99. The result of the research findings shows that the t-test value is higher than the t-table value. It implies that the research hypothesis is accepted. It means that the use of Small Group Discussion (SGD) technique can develop speaking skill to the tenth grade students of SMA Negeri 1 Bolano Parigi Moutong District.